DEPRESSÃO EM GESTANTES ATENDIDAS NA ATENÇÃO PRIMÁRIA À SAÚDE - Bianca Aparecida Brito da Silva; Walisete de Almeida Godinho Rosa; Iácara Santos Barbosa Oliveira; Monique Godinho Rosa; Nariman de Felício Bortucam Lenza; Vanessa Luzia Queiroz Silva (Universidade Federal do Paraná, 2020)
Objective: To identify the presence of depression in pregnant women accompanied by the prenatal care program in Primary Health Care. Method: A descriptive and exploratory study with a quantity-qualitative approach that was performed in two stages: application of the Beck Depression Inventory and semi-structured interview. The data were analyzed using simple descriptive statistics and content analysis. Results: The Beck Depression Inventory showed that, of the 67 interviewed pregnant women, 22 (33%) had depressive symptoms, 14 (64%) had mild to moderate depression, and two (9%) had severe depression. Two topics emerged from the interview: Gestational period experience, and Nursing consultation and prenatal mental health approach. Conclusion: The study showed that depression during pregnancy is frequent. Prenatal nursing consultation can be an opportunity for depression detection and early diagnosis and for improved care of the pregnant woman.